2022
DOI: 10.3390/molecules27020528
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Efficacy of Glass Ionomer Cement in Incorporation with Biogenic Zingiber officinale Capped Silver-Nanobiotic, Chlorhexidine Diacetate and Lyophilized Miswak

Abstract: In the present study, Zingiber officinale is used for the synthesis of Zingiber officinale capped silver nanoparticles (ZOE-AgNPs) and compares the antimicrobial efficacy and compressive strength of conventional glass ionomer cement (GIC) combined with ZOE-AgNPs, lyophilized miswak, and chlorhexidine diacetate (CHX) against oral microbes. Five groups of the disc-shaped GIC specimens were prepared. Group A: lyophilized miswak and GIC combination, Group B: ZOE-AgNPs and GIC combinations, Group C: CHX and GIC com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 41 publications
3
2
0
Order By: Relevance
“…Premkishore et al [11] and Saleh et al [12] reported the robust antibacterial activity of the ginger extract against Streptococcus mutans. Additionally, Hegde et al [13] [15], a finding consistent with our current study. The current study's results indicate that the antibacterial efficacy of ginger against Streptococcus mutans may stem from its valuable phytoconstituents, which exhibit a high affinity for the surface protein antigen of Streptococcus mutans.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Premkishore et al [11] and Saleh et al [12] reported the robust antibacterial activity of the ginger extract against Streptococcus mutans. Additionally, Hegde et al [13] [15], a finding consistent with our current study. The current study's results indicate that the antibacterial efficacy of ginger against Streptococcus mutans may stem from its valuable phytoconstituents, which exhibit a high affinity for the surface protein antigen of Streptococcus mutans.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, Ahmed et al and Azizi et al demonstrated noteworthy antibacterial activity against Streptococcus mutans , Staphylococcus spp., Lactobacillus spp., and Streptococcus sanguinis cariogenic microorganisms [ 14 ]. In 2022, Ashour et al revealed that combining GIC with active components of ginger extract and chlorhexidine could enhance antimicrobial properties effectively [ 15 ], a finding consistent with our current study. The current study's results indicate that the antibacterial efficacy of ginger against Streptococcus mutans may stem from its valuable phytoconstituents, which exhibit a high affinity for the surface protein antigen of Streptococcus mutans .…”
Section: Discussionsupporting
confidence: 91%
“…The use of NPs alone or in combination with a known antibiotic (amoxicillin) led to significantly improved results, both in term of antimicrobial efficiency (compared with GIC, but also with the use of amoxicillin by itself) and in terms of compressive strength (compared with GIC and amoxicillin), with superior results for the application of the composite than for the single use of NPs [ 46 ]. Similar results were obtained by Ashour et al [ 47 ] when evaluating the possibilities of incorporating AgNPs phytosynthesized using ginger extract in GIC. The authors observed an increase in both antimicrobial efficiency and compressive strength when surveying the potential of AgNPs and chlorhexidine compared with any of the components used by themselves.…”
Section: Resultssupporting
confidence: 88%
“…Furthermore, AgNPs and TVE-CuNPs were conjugated with the SH group in proteins and damageed nucleic acids. In the current research, and for the first time, as shown in Table 4 , GIC was combined with metronidazole and TVE-CuNPs or AgNPs, and the result demonstrates a significantly higher antimicrobial efficacy against the tested microbes when compared to the GIC with a single antimicrobial agent as well as the conventional GIC without any combinations [ 32 , 36 , 37 ]. Furthermore, the compressive strength difference across all GIC groups was statistically negligible ( p > 0.05).…”
Section: Discussionmentioning
confidence: 96%